Motivations, Mechanisms and Determinants of Terrorist Technology Transfer (National Consortium for the Study of Terrorism and Responses to Terrorism: A Department of Homeland Security Science and Technology Center of Excellence, 2017)
The Unconventional Weapons and Technology Division of the National Consortium for the Study of Terrorism and Responses to Terrorism (UWT-START) and the Swedish Defense Research Agency (FOI) collaborated to conduct a pilot research project examining the motivations, mechanisms and determinants of success that influence the transfer of technologies to terrorists
Keywords: Terrorismo